Motivation for physical culture as factor of students’ functional state optimization - O.G. Lachno (Physical Education of Students)
Purpose: to analyze students’ attitude to physical education classes; to compare motivation for physical education of 1 st and 4 th year students. Material: 100 students of 17 - 22 years’ age participated in the research. All they were questioned. Results: In the whole, boys have positive attitude to sport practicing but some of them can have harmful habits. The attitude to sport practicing of most of girls changes with age. It was found that biological age of students significantly exceeds passport age. Biological age of senior students it reduces to some extent, in comparison with junior students. It was also found that in process of studying at HEE students’ motivation for sport practicing changes to positive side. It witnesses about formation of student positive attitude to physical education in general. Conclusions: we have shown that there is a demand in strengthening of motivation for physical culture classes and further formation positive attitude to them with increasing of students’ knowledge about physical education.